Structural biology of FGF signaling in human development and disease - Mohammadi, Moosa (Henry Stewart Talks, 2007)
FGF family of ligands, and FGF receptor (FGFR) subfamily of receptor tyrosine kinase superfamily, The roles of FGF signaling in mammalian biology and diseases, FGFR receptor alternative splicing and its essential role in epithelial-mesenchymal signaling loop, and organogenesis, Structural mechanism by which FGF and heparan sulfate induce FGFR dimerization and activation on the cell surface, A working model for FGFR autoinhibition, Structural mechanisms by which FGF-FGFR binding specificity is achieved, Structural basis for how alternative splicing regulates ligand-binding specificity of FGFRs, Structural basis by which ligand-dependent pathogenic mutations in FGFR lead to receptor gain-of-function in human skeletal syndromes, Structural basis by which alternative splicing regulates patterning ability of FGF8 in the brain
Archived at 2018/12/10